The Effect of Self-Efficacy and Employee Engagement on Employee Performance in Mediation by Digital Literation - Iman Sidik Nusannas; Tjutju Yuniarsih; Janah Sojanah; Disman; Dhyah Mutmainnah; Muji Rahayu; Salman Imbari (Institute of Computer Science (IOCS), 2020)
This study aims to determine whether self-efficacy and employee engagement affect the performance of bank frontliners and is mediated by digital literacy. The research was conducted at ten national private bank branch offices in Bandung using a questionnaire distributed to 119 frontliners who handle digital transactions. The research results were processed using SPSS software using the path analysis method. The results showed that self-efficacy and performance had a positive and significant effect on digital literacy, while engagement had no significant effect on digital literacy. The output from the calculation results can be concluded that the efficacy significance value of 0.000 is smaller than 0.05, which can be concluded that there is an effect of self-efficacy (X1) on performance (Y). The efficacy significance value of 0.000 is smaller than 0.05, which can be concluded that there is an effect of engagement (X2) on performance (Y). The significance value of the self-efficacy variable (X1) is 0,000, the engagement variable (X2) is 0.133 and the performance variable (Y) is 0,000, so it can be concluded that only self-efficacy and performance have an effect on digital literacy (Z) while engagement (X2) has a value 0.133 which is greater than 0.05, so it can be concluded that engagement has no significant effect on digital literacy